Java based data monitoring system - Borbe, Dexter L. (1997)
The Java Based Data Monitoring System (JBDMS) is system for monitoring hardware acquired data on a Web page. This means that it allows a user to monitor data from any location that has access to the Internet. The system involves a Java applet, a server computer , a Java application program on the server computer, and the hardware for acquiring data. The server computer polls the data from the data acquisition hardware, which are connected to the server PC's serial ports. The Java applet, which can be accessed on the Internet, enables the user to request the server PC for data. This system has user configurable features, a user-friendly graphical interface, and allows the user to monitor more than one source of data. The limitation is that the sources of data must be connected to the same computer, which is the server PC. It is assumed that the reader of this document is familiar with Object-Oriented programming concepts, as well as some of the terminology used in computer networking.